Mediating roles of corneal biomechanical and topographic parameters in eye rubbing and keratoconus based on the Chinese keratoconus cohort study - Yang, Kaili; Tu, Runqi; Xu, Liyan; Gu, Yuwei; Fan, Qi; Yin, Shanshan; Yuan, Yi; Chang, Anqi; Wang, Yifan; Yin, Chenchen; Zang, Yonghao; Pang, Chenjiu; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeStudies have shown that eye rubbing is associated with increased risk of keratoconus (KC). However, the potential mediating roles between eye rubbing and KC remain largely unknown. Hence, this study aims to explore the mediating roles of two specific factors, namely, the inverse of the stiffness parameter at the first applanation (-SPA1) and maximal corneal keratometry (Kmax) values, in the relationship between eye rubbing and KC.MethodsA total of 395 patients with KC and 396 controls from the Chinese keratoconus (CKC) cohort study were included in this case–control analysis. The Spearman correlation and generalized linear regression models were used to analyze the associations between the time of eye rubbing, -SPA1, Kmax, and KC. Furthermore, three mediation models (individual, parallel multiple, and serial multiple) were utilized to investigate the mediating roles of -SPA1 and Kmax in the relationship between eye rubbing and KC.ResultsAfter adjusting for confounding factors, the odds ratio and 95% confidence interval (CI) for the time of eye rubbing, -SPA1, and Kmax in relation to KC were 1.02 (1.01, 1.04), 1.16 (1.12, 1.19), and 3.86 (2.52, 5.92), respectively. The individual mediation model indicated that the indirect effects of -SPA1 and Kmax were 0.084 and 0.056, respectively. The parallel multiple mediation model showed a total indirect effect of 0.081 for -SPA1 and Kmax. Additionally, the serial multiple mediation model (time of eye rubbing → -SPA1 → Kmax → KC) indicated that following -SPA1, Kmax partially mediated the relationship between the time of eye rubbing and KC with a total indirect effect of 0.024 (95% CI: 0.016–0.042), accounting for 14.5% of the total effect (time of eye rubbing on KC), while no significant indirect effect was found for Kmax alone.ConclusionsThe individual, parallel multiple, and serial multiple mediation analyses consistently demonstrated the mediating roles of -SPA1 and Kmax in linking the duration of eye rubbing to KC. Notably, the serial mediation pathway (time of eye rubbing → -SPA1 → Kmax → KC) exhibited a significant indirect effect. These findings confirm and complement the theoretical framework linking eye rubbing to KC, providing a reference for further exploration of the pathogenesis of KC.